(3GdQhVI GdRgjI aj PcQ hdGI eUQ hGdbGgQI GdeYRjIs - (3TeS GdOjf eMeO Hf CMeO Hf CHj GdSQhQ GdHcQj,J (B1060 (3g` s ((3TQa GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CeO GdOjGQ GdeUQjI HGdYWGA s
(3HChdg LOhGd Hef Jhdi Ydi eUQ ef GdhdGI GdYKeGfjf hbO hUd ajg GdeDda Edi hdGjI Ydi HGTG GdeJhdj SfI (B1060 (3hHYOg JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B77 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdJjehQjI (B((3eUhQ Yf GdaGJjcGf(B) ((3JGQjN (B2407) s
Keywords: (3GdJGQjNs